Factors Predicting Cerebrospinal Fluid Leaks in Microvascular Decompressions: A Case Series of 1011 Patients. Issue 3 (9th March 2023) - Xu, Risheng; So, Raymond J.; Materi, Joshua; Nair, Sumil K.; Alomari, Safwan O.; Huang, Judy; Lim, Michael; Bettegowda, Chetan
Abstract : BACKGROUND: Microvascular decompression (MVD) using a retrosigmoid approach is a highly effective, open-surgical procedure for neurovascular conflict in the posterior fossa, although there is a risk of postoperative cerebrospinal fluid (CSF) leak. OBJECTIVE: To identify factors associated with postoperative CSF leakage after MVD. METHODS: We retrospectively reviewed all patients who underwent MVDs at our institution from 2007 to 2020. Patient demographics, clinical diagnoses, and procedural characteristics were recorded and compared. Factors leading to CSF leak were analyzed using χ 2, univariate, and multivariate regression. RESULTS: Of 1011 patients who underwent MVDs, 37 (3.7%) presented with postoperative CSF leaks. In univariate analysis, the use of Cranios/Norian to obliterate the air cells was protective against CSF leak ( P = .01). Craniotomies ( P = .002), the use of dural substitutes such as Durepair ( P = .04), dural onlays such as DuraGen ( P = .04), muscle/fascia ( P = .03), and titanium mesh cranioplasty >5 cm ( P = .03) were associated with CSF leak. On multivariate analysis, only the presence of craniotomies ( P = .04) and nonprimary dural closure ( P = .03) were significant risk factors for CSF leak. When excluding the 34 (3.4%) patients who underwent a craniotomy, the lack of primary dural closure still remained significantly associated with postoperative CSF leak ( P = .04). CONCLUSION: Our results represent one of the largest series of posterior fossa surgeries for a uniform indication in North America. Our study demonstrates increased risk for postoperative CSF leak when craniotomies are performed and when primary dural closure is not established. Given the small sample of patients who received a craniotomy, however, future studies corroborating this finding should be performed.